Dose- and duration-dependent cytotoxicity and genotoxicity in human hepato carcinoma cells due to CdTe QDs exposure. (August 2019) - Katubi, KM; Alzahrani, FM; Ali, D; Alarifi, S
Nanotechnology has achieved more commercial attention over recent years, and its application has increased concerns about its discharge in the environment. In this study, we have chosen human hepatic carcinoma (HuH-7) cells because liver tissue has played an important role in human metabolism. Therefore, the objective of this study was to determine DNA damaging and apoptotic potential of cadmium telluride quantum dots (CdTe QDs; average particle size (APS) 10 nm, 1–25 µg/ml) on HuH-7 cells and the basic molecular mechanism of its cellular toxicity. Cytotoxicity of different concentrations of CdTe QDs on HuH-7 cells was determined by 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) and lactate dehydrogenase (LDH) tests. Moreover, reactive oxygen species (ROS) generation, mitochondrial membrane potential, DNA damage, and Hoechst 33342 fluorescent staining morphological analysis of necrotic/apoptotic cells were detected; cellular impairment in mitochondria and DNA was confirmed by JC-1 and comet assay, respectively. A dose- and time-dependent cytotoxicity effect of CdTe QDs exposure was observed HuH-7 cells; the significant ( p < 0.05) cytotoxicity was found at 25 μg/ml of CdTe QDs exposure. The percentage of cytotoxicity of CdTe QDs (25 μg/ml) in HuH-7 cells reached 62% in 48 h. CdTe QDs elicited intracellular ROS generation and mitochondrial depolarization, and DNA integrity cells collectively advocated the apoptotic cell death at higher concentration. DNA damage was observed in cells due to CdTe QDs exposure, which was mediated by oxidative stress. This study exploring the effects of CdTe QDs in HuH-7 cells has provided valuable insights into the mechanism of toxicity induced by CdTe QDs.